The sources of scepticism - Pritchard, Duncan; Raga Rosaleny, Vicente (Estudios de Filosofía, 2019)
It is claimed that the radical sceptical problem that is the focus of much of contemporary epistemological discussion in fact divides into two logically distinct subproblems —a formulation that turns on the closure principle, and a second formulation which turns on the underdetermination principle. The Wittgensteinian account of the structure of rational evaluation is set out, and it is shown how this proposal —at least when properly formulated—can deal with closure-based radical scepticism. It is also claimed, however, that this account fails to gain any purchase on underdetermination-based radical scepticism. The antidote to this latter form of radical scepticism lies elsewhere—with, it is suggested, epistemological disjunctivism.